2007
DOI: 10.1007/s11425-007-2028-6
|View full text |Cite
|
Sign up to set email alerts
|

On quasi-similarity of subnormal operators

Abstract: For a compact subset K in the complex plane, let Rat(K) denote the set of the rational functions with poles off K. Given a finite positive measure with support contained in K, let R 2 (K, ν) denote the closure of Rat(K) in L 2 (ν) and let Sν denote the operator of multiplication by the inde-Suppose Ω is a bounded open subset in the complex plane whose complement has finitely many components and suppose Rat(Ω) is dense in the Hardy space H 2 (Ω). Let σ denote a harmonic measure for Ω. In this work, we character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In 1991 J. Thomson first proved Theorem 1 for P 2 (µ) except 4) and 5) in [20]. Some applications of Theorem 1 can be found in [14,17].…”
Section: A Structure Theorem For the Mean Closure Of The Rational Funmentioning
confidence: 99%
“…In 1991 J. Thomson first proved Theorem 1 for P 2 (µ) except 4) and 5) in [20]. Some applications of Theorem 1 can be found in [14,17].…”
Section: A Structure Theorem For the Mean Closure Of The Rational Funmentioning
confidence: 99%
“…Originally motivated by a research problem in operator theory suggested by Ronald Douglas: Can the similarity and quasi-similarity of the well-known results of W. Clary be extended to multiply connected domains? The readers may consult [4][ p. 370-373] and [5,6,7,8,9] for the topics. The quasi-similarity case was first investigated in [5] and then later in [8], but the similarity case was only to be done recently in [9] and the extension was completed because of the research in this work.…”
Section: Introductionmentioning
confidence: 99%
“…The readers may consult [4][ p. 370-373] and [5,6,7,8,9] for the topics. The quasi-similarity case was first investigated in [5] and then later in [8], but the similarity case was only to be done recently in [9] and the extension was completed because of the research in this work. We consider the following problem: What are the natural extension of the Carleson measures from circular domains to general domains.…”
Section: Introductionmentioning
confidence: 99%
“…One needs to have them when applying it to operator theory. For example, see [17] and [24]). In [6], Conway and Elias studied the same problem as that in this paper.…”
Section: Introductionmentioning
confidence: 99%